Building Community Capacity in Bereavement Support: Lessons Learnt From Bereaved Caregivers - Breen, Lauren; Aoun, Samar; Rumbold, Bruce; McNamara, Beverley; Howting, Denise; Mancini, Vincent (2017)
BACKGROUND: Most bereaved people do not require specialist intervention, yet building community capacity in providing bereavement support is underdeveloped. While family caregivers indicate a need for more information about bereavement, there is little evidence to guide what this information might contain. OBJECTIVE: The study's purpose was to inform bereavement support by determining the advice people bereaved through expected deaths in palliative care have for others in that situation. DESIGN: Four funeral providers posted a questionnaire to previous clients who had used their services 6 to 24 months prior and 678 bereaved people responded. SETTING/PARTICIPANTS: The sample size for this study comprised 265 bereaved people whose relative used palliative care services. MEASUREMENTS: The questionnaire comprised 82 questions about caregiving, bereavement support, current bereavement-related distress, and 2 open-ended questions concerning their bereavement, one of them on advice they have to other people in the same situation. RESULTS: Family caregivers (n = 140) of people who received palliative care responded to the open-ended question about advice for others. An open content analysis yielded 3 themes-preparations for bereavement, utilizing social networks, and strategies for dealing with grief. CONCLUSIONS: Bereaved family caregivers' experiential knowledge can be harnessed to progress the development of bereavement care strategies for the good of the community. These responses could be incorporated into information brochures, posters, and other community education avenues in order to upskill palliative care bereavement volunteers and the wider community so that bereaved family caregivers are best supported.